Evaluate the sum: $$\sum^{\infty}_{k=0}(k+1)x^{k}$$

Now my attempt was to start with a series we know, like the geometric series. so $$\sum_{k=0}^{\infty}x^k=\frac{1}{1-x}$$ I also think there is a generic form of the form $$\sum_{k=0}^{\infty}a_kx^k=\frac{a}{1-x}$$

I am not exactly sure how to manipulate this known series to reach some conclusive summation for the sum I am being asked to evaluate. I have done simpler examples where you simply differentiate and than multiply through by x and the solution is there. But I do not know what to do here to find the sum, I would appreciate some tips or advice.


$$\begin{align} f(x)&=\sum_{k=0}^\infty x^{k+1}&&=\frac{x}{1-x}\\ f'(x)&=\sum_{k=0}^\infty (k+1)x^k&&=\left(\frac{x}{1-x}\right)'\\ \end{align}$$

  • $\begingroup$ okay so I differentiate and I get $$\frac{1}{(1-x)^2}$$ now what value do I plug in in order to find the actual sum of this series or is the sum just $$\frac{1}{(1-x)^2}$$. I was under the impression that it is suppose to be a number. $\endgroup$ – B ry Oct 27 '16 at 18:20
  • $\begingroup$ @Bry Yeah that's the sum. It's is dependent on $x$ so it can't be a single number. If you had $x=0.5$, you'd get a sum of $4$ but with $x=0.75$, you get a sum of $16$. That's partly why I wrote it as $f(x)$, since I think it's a bit clearer that way. But as MitchellSpector says, you can do it without needing any calculus. Cool? $\endgroup$ – Jam Oct 27 '16 at 18:24
  • $\begingroup$ what about something like $$\sum_{k=0}^{\infty}(-1)^k(k+1)x^{2k}$$ $\endgroup$ – B ry Oct 27 '16 at 18:37
  • $\begingroup$ @Bry Not sure about that one off the top of my head but try reading the link SeanRobertson posted about Generating Functions, which tells you a lot about these types of series. $\endgroup$ – Jam Oct 27 '16 at 18:46
  • $\begingroup$ @Bry I added an addendum to my answer to show how $\sum_{k=0}^{\infty}(-1)^k(k+1)x^{2k}$ can be computed from the first sum. $\endgroup$ – Mitchell Spector Oct 27 '16 at 19:54

There's no need to use derivatives.

Set $$S=1+2x+3x^2+4x^3+\dots$$ and subtract

$$xS=\hphantom{1+2}x+2x^2+3x^3+\dots$$ to get

$$(1-x)S=1+x+x^2+x^3+\dots = \frac1{1-x},$$

so your sum is


This is valid for $-1\lt x\lt 1.$


As for $\sum_{k=0}^{\infty}(-1)^k(k+1)x^{2k},$ which you asked about in a comment, this follows from the first sum:

\begin{align}\sum_{k=0}^{\infty}(-1)^k(k+1)x^{2k} &= \sum_{k=0}^{\infty}(k+1)(-x^2)^{k} \\&=\frac1{(1-(-x^2))^2} \\&==\frac1{(1+x^2)^2}, \end{align}

again for $-1\lt x\lt 1.$


To avoid repetition, we know that


As for the last part, if we have

$$f(x)=\sum_{k=0}^\infty a_kx^k$$

then $f(x)$ is analytic, assuming it converges for some $x$ with radius of convergence greater than $0$.

According to Taylor's theorem, we then have


More generally, we have


where $f^{(n)}(x)$ is the $n^{\text{th}}$ derivative of $f$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.